A new assignment of free links in Midimew connected mesh network - Awal, Md. Rabiul; Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Sembok, Tengku Mohd; Akhand, M. A. H (2014)
A Midimew connected Mesh Network (MMN) is a MInimal DIstance MEsh with Wrap-around links network of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher-level networks. In this paper, we present a new assignment of free links to form the higher level networks of the MMN (called HMMN), addressing of node, routing of message, and evaluate the static network performance of the HMMN, its counter rival VMMN, TESH, mesh, and torus networks. It is shown that the proposed HMMN possesses several attractive features, including constant degree, small diameter, low cost, small average distance, moderate bisection width, and same fault tolerant performance than that of other conventional and hierarchical interconnection networks. It is also shown that with the same node degree, arc connectivity, bisection width, and wiring complexity, the diameter and average distance of the HMMN is lower than that of the TESH network and trivially higher to that of VMMN.